The Reception of W. B. Yeats in Croatia - Gjurgjan, Ljiljana Ina (2006)
The article discusses the four phases in the reception of W. B. Yeats's poetry in Croatia, the first ending at the close of WW II, the second lasting until 1960s. In the third phase the reception grows considerably and his work influences the generation of transaltors and scholars born around 1930s. The fourth phase is marked by the work of scholars born around 1950, their work being published in the 1980s or later, looking into Yeats's work from a theoretical point of view.
Projekt MZOS
ENG